2009
DOI: 10.1016/j.neuroscience.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-elicited cataplexy in orexin knockout mice

Abstract: Mice lacking orexin/hypocretin signaling have sudden episodes of atonia and paralysis during active wakefulness. These events strongly resemble cataplexy, episodes of sudden muscle weakness triggered by strong positive emotions in people with narcolepsy, but it remains unknown whether murine cataplexy is triggered by positive emotions. To determine whether positive emotions elicit murine cataplexy, we placed orexin knockout (KO) mice on a scheduled feeding protocol with regular or highly palatable food. Baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 43 publications
0
41
0
1
Order By: Relevance
“…Modeling of orexin neuron activity suggests that dynorphin is capable of modulating orexin responses, delaying its arousal effects at the sleep/wake transition by affecting the sensitization and firing rate of orexinsensitive neurons (Williams and Behn, 2011). Nevertheless, orexin peptide knockout animals have provided a useful model in which to study the cataplectic episodes in detail, where both scheduled palatable food and running wheel presentation effectively increase the frequency of cataplectic episodes, presumably mimicking the effect of positive emotions in human patients (Españ a et al, 2007;Clark et al, 2009). Consistent with this observation is the finding that both positive and negative olfactory stimuli (female and coyote urine) are also sufficient to induce narcoleptic episodes in male orexin peptide knockout mice (Morawska et al, 2011).…”
Section: The Role Of the Hcrt Gene And Hcrt Gene Productmentioning
confidence: 99%
“…Modeling of orexin neuron activity suggests that dynorphin is capable of modulating orexin responses, delaying its arousal effects at the sleep/wake transition by affecting the sensitization and firing rate of orexinsensitive neurons (Williams and Behn, 2011). Nevertheless, orexin peptide knockout animals have provided a useful model in which to study the cataplectic episodes in detail, where both scheduled palatable food and running wheel presentation effectively increase the frequency of cataplectic episodes, presumably mimicking the effect of positive emotions in human patients (Españ a et al, 2007;Clark et al, 2009). Consistent with this observation is the finding that both positive and negative olfactory stimuli (female and coyote urine) are also sufficient to induce narcoleptic episodes in male orexin peptide knockout mice (Morawska et al, 2011).…”
Section: The Role Of the Hcrt Gene And Hcrt Gene Productmentioning
confidence: 99%
“…Interventions that significantly increase cataplexy frequency have included stimuli intended to evoke strong emotions, such as novel environments (Mieda et al, 2004), controlled access to running wheels (Espana et al, 2007), highly palatable food (Clark et al, 2009) including chocolate (Oishi et al, 2013; Tabuchi et al, 2014), the combination of chocolate and running wheels (Burgess et al, 2013), and attractive or aversive odors (Morawska et al, 2011). While chocolate has been shown to be highly effective at increasing cataplexy from 1.6-fold (Tabuchi et al, 2014) to 8.1-fold (Oishi et al, 2013), it could potentially confound studies by introducing dietary changes or secondary effects of prolonged wakefulness.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Studies have shown that central orexin injections induce feeding in rats and mice (1,2). Conversely, central administration of orexin receptor-1-selective antagonist greatly reduced food intake in rats (31), whereas orexinknockout and orexin neuronal-ablated mice exhibit reduced feeding behavior (32)(33)(34)(35). Other studies suggest that orexin neurons are sensitive to energy status cues, such as glucose levels (31).…”
Section: Orexin and Feedingmentioning
confidence: 99%